2016
DOI: 10.1007/s12220-016-9712-0
|View full text |Cite
|
Sign up to set email alerts
|

Solvability of Minimal Graph Equation Under Pointwise Pinching Condition for Sectional Curvatures

Abstract: Abstract. We study the asymptotic Dirichlet problem for the minimal graph equation on a Cartan-Hadamard manifold M whose radial sectional curvatures outside a compact set satisfy an upper boundand a pointwise pinching conditionfor some constants φ > 1 and C K ≥ 1, where P and P are any 2-dimensional subspaces of TxM containing the (radial) vector ∇r(x) and r(x) = d(o, x) is the distance to a fixed point o ∈ M . We solve the asymptotic Dirichlet problem with any continuous boundary data for dimensions n = dim M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The interested reader may consult [7,Thm. 1.5] and [7,9], as well as [27] for related interesting non-existence results. This naturally motivates the following Question.…”
Section: Introductionmentioning
confidence: 95%
“…The interested reader may consult [7,Thm. 1.5] and [7,9], as well as [27] for related interesting non-existence results. This naturally motivates the following Question.…”
Section: Introductionmentioning
confidence: 95%
“…Recently the asymptotic Dirichlet problem for minimal graph, f -minimal graph, p-harmonic and A-harmonic equations has been studied for example in [22], [30], [31], [7], [21], [8], [6], [5], and [17], where the existence of solutions was studied under various curvature assumptions and via different methods. In [8] the existence of solutions to the minimal graph equation and to the A-harmonic equation was proved in dimensions n ≥ 3 under curvature assumptions − log r(x)) 2ε r(x) 2 ≤ K(P x ) ≤ − 1 + ε r(x) 2 log r(x)…”
Section: Introductionmentioning
confidence: 99%
“…Cheng [5] was the first to solve the problem for the Laplacian under the same type of pointwise pinching assumption for the sectional curvatures as we consider in this paper. Later the asymptotic Dirichlet problem has been generalized for p-harmonic and A-harmonic functions and for minimal graph equation under various curvature assumptions, see [2], [3], [10], [11], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…where φ > 1 is constant. In [2] the authors showed that, with these weaker assumptions, the solvability result holds also for the minimal graph equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation